Association of New York Scientists newsletter, February 28, 1947 - Association of New York Scientists (1947)
Poll from the Association of New York Scientists, asking scientists and engineers their opinion on atomic bombs and atomic energy.
Keywords: Association of New York Scientists; Newsletters; Lilienthal, David Eli, 1899-1981; Nuclear energy